Dose Optimization for Near-Infrared Fluorescence Sentinel Lymph Node Mapping in Melanoma Patients - van der Vorst, J.R. (2013)
BACKGROUND: Regional lymph node involvement is the most important prognostic factor in cutaneous melanoma. Since only 20% of melanoma patients have occult nodal disease and would benefit from a regional lymphadenectomy, the sentinel lymph node (SLN) biopsy was introduced. NIR fluorescence has been hypothesized to improve SLN mapping. OBJECTIVES: To assess the potential of intraoperative near-infrared (NIR) fluorescence imaging to improve SLN mapping in melanoma patients and to examine the optimal dose of indocyanine green adsorbed to human serum albumin (ICG:HSA). METHODS: Fifteen consecutive cutaneous melanoma patients underwent the standard SLN procedure using (99m)technetium-nancolloid and patent blue. In addition, intraoperative NIR fluorescence imaging was performed after injection of 1.6 mL of 600, 800, 1000 or 1200 μM of ICG:HSA in four quadrants around the primary excision scar. RESULTS: NIR fluorescence SLN mapping was successful in 93% of patients. In one patient, no SLN could be identified using either conventional methods or NIR fluorescence. A total of 30 SLNs (average 2.0, range 1-7) were detected, 30 radioactive (100%), 27 blue (73%), and 30 NIR fluorescent (100%). With regard to the effect of concentration on SBR a trend (P = 0.066) was found favouring the 600, 800 and 1000 μM groups over the 1200 μM group. CONCLUSION: This study demonstrates feasibility and accuracy of SLN mapping using ICG:HSA. Considering safety, cost, and pharmacological characteristics, an ICG:HSA concentration of 600 μM appears optimal for SLN mapping in cutaneous melanoma, though lower doses need to be assessed.